Profitability and Resource Use Efficiency of Poultry Egg Production in Abuja, Nigeria - J.N., Nmadu; I.O., Ogidan; R.A., Omolehin (Kasetsart Journal of Social Sciences, 2014)
The profitability, break-even point, elasticity of production, and resource use efficiency of poultry egg production by poultry egg farmers was determined in Abuja. Primary data were collected from 62 farmers drawn from the area of study by a simple random sampling technique. Analysis of data was carried out via the use of descriptive statistics, multiple regression, costs and returns analysis (budgeting), and break-even analysis. The costs and returns analysis indicated that an average farmer invested annually NGN (Nigerian naira currency) 3,504,352 (USD 1 is approximately NGN 160) in poultry egg production. The gross margin, net income, and gross return invested were NGN 10,875,663, NGN 9,798,772 and 1.72 respectively. These figures suggest that egg production in the study area was profitable. The study also showed that the break-even point for an average poultry egg farmer in Abuja was 3,978 crates of eggs per annum and the margin of safety ratio was 89 percent. In addition, the results of the study revealed that poultry egg farmers had positive, decreasing returns to scale (0.508) in egg production which indicated that poultry egg production was in the rational stage of production (Stage 2). Poultry production was profitable in Abuja but the farmers were not fully efficient in the use of their resources. To improve the profitability and resource use efficiency of poultry production, it was recommended that poultry egg farmers should implement better management practices to minimize the incidence of disease outbreaks, thereby reducing the cost of production.